STUDY OF GENETIC VARIABILITY PARAMETERS IN COWPEA (VIGNA UNGUICULATA L. WALP.) GERMPLSAM LINES - HASAN KHAN,; K. P. VISWANATHA,; H. C. SOWMYA, (The Bioscan, 2015)
A genetic variability study is carried out with a set of 196 cowpea genotypes and analysis of variance revealed significant differences among the genotypes tested for all the nine characters, justifying the selection of genotypes for the study. The genotypes exhibits considerable amount of genetic variation for all the characters and it indicated the good scope for selection of suitable basic material for further improvement. PCV values were of higher magnitude than GCV for all the characters under study. The estimates of PCV and GCV were high for number of pods per plant, pod length, plant height, number of branches per plant, test weight and seed yield per plant. High heritability and high genetic advance as per cent (GAM) of mean was observed for number of pods per plant, number of seeds per pod, pod length, plant height, number of branches per plant, test weight and seed yield per plant. These characters are governed by additive gene action and one should go for direct selection for these traits to improve in future.